Adopting opportunity cost as a tool to increase tax revenue: Applied research in the General Tax Authority - Companies Division (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This research seeks to try to address one of the important issues in society that prevents the state from achieving its social, economic, political and financial goals, represented by the low tax proceeds, through which it can achieve those goals. What is reflected on the tax proceeds, knowing that the General Tax Authority does not take into account the issue of analyzing the opportunity cost of corporate capital as one of the profit indicators when setting the annual controls, which leads to a decrease in the tax proceeds, and therefore the research objective will be to shed light on the importance of adopting the concept of analysis The opportunity cost by the General Tax Authority to achieve a tax proceeds commensurate with the number of those companies in Iraq and the amount of their capital, and at the same time motivating and encouraging limited companies that do not have any economic activity to search for alternative opportunities to invest their capital and turn their losses into profits.